Experiment and modeling of vapor–liquid equilibria for H2O+CH3OH+KCl and H2O+CH3OH+NaBr systems. (December 2018) - Xu, Xianzhen; Zhou, Yu; Wang, Zonghua; Wang, Xi
Abstract: In this work, vapor–liquid equilibrium (VLE) data were reported on mixed solvent electrolyte systems containing H2 O+CH3 OH+KCl and H2 O+CH3 OH+NaBr. The measurements were carried out in a computer-controlled glass apparatus. A new model based on UNIQUAC equation was proposed for the correlation of vapor–liquid equilibria in mixed solvent electrolyte systems. The model for the excess Gibbs energy was modified from the UNIQUAC equation, and the activity coefficients were calculated by UNIQUAC terms and solvent-solution effect terms. In addition, an assumption for the solution effect was introduced into this model. Experiment and literature data for mixed solvent electrolyte systems were successfully correlated using the proposed model.